ANALISA KEBUTUHAN DAN SPESIFIKASI TEKNIS POMPA UMPAN HYDROLIZER PADA PUSRI EFFLUENT TREATMENT PLANT - Marbun, Richard (MACHINERY Jurnal Teknologi Terapan, 2023)
PT Pupuk Sriwidjaja Palembang has a plant effluent treatment facility called Pusri Effluent Treatment (PET) Plant. The effluent streams come from Urea and Ammonia plants and are fed to PET using Effluent Hydrolizer Feed Pump GA-701. The objective of this analysis is to obtain the relevant and optimum pump’s technical requirements and specifications for accommodating the plant operating requirement. Using literature research, field research, and technical discussions, the optimal specifications of the GA-701 pump can be determined. The rated design point of the pump is 55 m3/hour at a head of 260.8 m, with an efficiency greater than 52.9% and an NPSHr less than 9.6 m. For reliability, the pump construction type is a between-bearing multistage type with SS316 material for the wetted parts and supported by the use of a mechanical seal with API Flush Plan 32.